ASSESSMENT OF SOCIO-ECONOMIC DEVELOPMENT AND ENVIRONMENTAL SECURITY OF THE REGION (ON THE EXAMPLE OF ATYRAU REGION) - Igaliyeva, L.N. (Academic Journal of Physical and Chemical Sciences, 2018)
The socioeconomic development of the region is an integral part of the development of the national economy. Adaptations of various processes of effective management of economic entities occur, as a rule, at lower levels of socioeconomic systems. The study of best practices in the development of regions is relevant and in demand in the current economic conditions. Such economic development leads to the emergence of environmental problems, impedes the sustainable development of the region. Problems arise when the anthropogenic load on the territory of Atyrau region exceeds its ecological capabilities, due to the natural resource potential and the general stability of natural complexes to man-caused stresses. The development of the economy is connected with the impact on the environment, as the creation of new and expansion of existing production leads to positive economic and social results, but it also has negative aspects, in particular, the environmental situation may worsen. Therefore, an important scientific problem is the assessment of the impact of economic development on the environment. The article deals with the concept of social and economic potential. The urgency of the social and economic development of the region is determined. The calculations of the change in the gross regional product per capita, the structure of the GRP, and the indices of the volume of industrial production in the Atyrau region were made. Also, the main constituent elements of the environmental safety of the region were identified, and the ecological and economic situation of the region was assessed.